Anti-corrosion hydrogen conveying pipeline based on stainless steel substrate and preparation method of anti-corrosion hydrogen conveying pipeline

By setting up a multi-layer coating structure on the stainless steel substrate, including an enamel layer, a hydrogen resistance layer and a corrosion-proof layer, the problems of hydrogen damage and insufficient binding force are solved, and high-efficiency hydrogen barrier and corrosion-proof performance are achieved to meet the needs of the submarine environment.

CN119144956AActive Publication Date: 2024-12-17LIAOCHENG ANTAI PETROLEUM MACHINERY

Patent Information

Application Number
CN202411630084.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-17
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Stainless steel substrates are prone to hydrogen damage in high-pressure hydrogen environments, resulting in material strength reduction and leakage problems. The existing hydrogen-resistance coatings lack binding strength in the subsea environment, making it difficult to adapt to the long-term service requirements of subsea hydrogen transport pipelines.

Method used

Using a multi-layer coating structure, including an inner surface enamel layer and an outer surface anticorrosion layer, through a Ni-Ti-Ce transition layer, a hydrogen-retardant layer and a modified epoxy organic coating, combined with inorganic silicone adhesive, graphene oxide and rare earth oxide It forms an efficient hydrogen barrier and corrosion protection system to enhance the bonding and corrosion resistance of the material.

Benefits of technology

It realizes the efficient hydrogen barrier and corrosion resistance of stainless steel matrix pipelines in the subsea environment, improves the hydrogen resistance and corrosion resistance of the materials, and ensures the safety and reliability of the subsea hydrogen transmission pipeline.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144956A_ABST
    Figure CN119144956A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-corrosion hydrogen conveying pipeline based on a stainless steel substrate and a preparation method of the anti-corrosion hydrogen conveying pipeline, and belongs to the technical field of marine industry metal materials. The anti-corrosion hydrogen conveying pipeline based on the stainless steel base body comprises a stainless steel base body pipe, an inner surface coating and an outer surface coating, wherein the inner surface coating and the outer surface coating are arranged on the stainless steel base body pipe. The inner surface coating sequentially comprises an enamel layer, a hydrogen-resistant layer and a transition layer from inside to outside; the outer surface coating sequentially comprises a transition layer, a first anti-corrosion layer and a second anti-corrosion layer from inside to outside. By arranging the inner surface coating and the outer surface coating, the technical effects of internal hydrogen resistance and external corrosion resistance are achieved; the transition layer enhances the binding force between the hydrogen-resistant layer and the stainless steel substrate and the binding force between the first anticorrosive layer and the stainless steel substrate; the hydrogen-resistant layer and the enamel layer jointly realize comprehensive hydrogen permeation resistance; under the combined action of the first anti-corrosion layer and the second anti-corrosion layer, the stainless steel base body seabed hydrogen conveying pipeline can adapt to the seabed working environment and has high corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a corrosion-resistant hydrogen transmission pipeline based on a stainless steel substrate and a preparation method thereof, and belongs to the technical field of metal materials for the marine industry. Background Art

[0003] Stainless steel is often used in high-pressure hydrogen systems due to its excellent corrosion resistance and plasticity. However, hydrogen pipelines and other materials are exposed to high-pressure (1.0-4.0MPa) hydrogen environments for a long time. Hydrogen can easily penetrate into the interior of their structural materials and interact with the components and structures in the materials, resulting in a decrease in mechanical properties such as strength and plasticity, causing cracks or brittle fractures in the materials, which is the so-called hydrogen damage. This ultimately leads to leakage and other problems, which can cause major safety accidents, casualties, economic losses and other problems.

[0004] In the prior art, the surface of the structural material is usually covered with one or more layers of hydrogen barrier coatings with low hydrogen permeability to prevent or delay the penetration and diffusion of hydrogen into the structural material, while retaining the structural properties of the base material. However, local damage, damage and shedding of the hydrogen barrier coating can easily cause the hydrogen barrier coating to fail. Good bonding strength is also required between the hydrogen barrier coatings and between the hydrogen barrier coatings and the base structural material to avoid problems such as coating shedding. Therefore, good film-base bonding strength is also an important characteristic that the hydrogen barrier coating needs to have.

[0005] Regarding the design of submarine hydrogen pipeline materials, since the transportation equipment is in the submarine environment, it is not easy to maintain and replace frequently. Also, since seawater itself is corrosive to a certain extent, how to obtain a stainless steel-based submarine hydrogen pipeline with a high hydrogen barrier factor, strong bonding force and the ability to adapt to the submarine environment is the premise and guarantee for realizing hydrogen energy application. Summary of the invention

[0006] In order to solve the above problems, an anti-corrosion hydrogen pipeline based on a stainless steel substrate and a preparation method thereof are provided. The anti-corrosion hydrogen pipeline based on a stainless steel substrate achieves the technical effects of internal hydrogen resistance and external corrosion resistance by arranging an inner surface coating and an outer surface coating; the enamel layer and the hydrogen barrier layer jointly achieve comprehensive hydrogen penetration resistance; the first anti-corrosion layer and the second anti-corrosion layer work together to enable the stainless steel substrate submarine hydrogen pipeline to adapt to the working environment of the seabed and have strong corrosion resistance.

[0007] According to one aspect of the present application, there is provided an anti-corrosion hydrogen transport pipeline based on a stainless steel substrate, comprising a stainless steel substrate pipe and an inner surface coating and an outer surface coating arranged on the stainless steel substrate pipe; The inner surface coating includes, from the inside to the outside, an enamel layer, a hydrogen barrier layer and a transition layer in sequence; the outer surface coating includes, from the inside to the outside, a transition layer, a first anti-corrosion layer and a second anti-corrosion layer in sequence; The transition layer is a Ni-Ti-Ce layer; The hydrogen barrier layer is prepared from inorganic silica adhesive, modified graphene oxide and oxide powder; The enamel layer is prepared from SiO2, metal oxides and borax; The first anti-corrosion layer is prepared from inorganic silicone adhesive, α-Al2O3, SiO2, low-temperature glass powder and titanate coupling agent; The second anti-corrosion layer is a modified epoxy organic coating.

[0008] Specifically, the thickness of the enamel layer is not less than 50 μm; the thickness of the hydrogen barrier layer is 50-150 μm; the thickness of the transition layer is 10-15 μm; the thickness of the first anti-corrosion layer is 50-100 μm; and the thickness of the second anti-corrosion layer is 200-300 μm.

[0009] Specifically, the transition layer is a Ni-Ti-Ce layer. On the one hand, Ni and Ti have similar crystal structures and atomic radii to the stainless steel matrix, have good compatibility, can form good chemical bonds at the interface, and have good bonding strength between the transition layer and the stainless steel matrix. On the other hand, Ni and Ti also have high chemical activity. Nickel and titanium can react chemically with the hydrogen barrier layer and the first anti-corrosion layer's SiO2, Al2O3, low-temperature glass powder and other components to form chemical bonds such as Ni-O-Si, Ti-O-Si, Ni-O, and Ti-O. Therefore, there is a strong bonding strength between the transition layer and the hydrogen barrier layer, and between the transition layer and the first anti-corrosion layer. The transition layer enhances the bonding performance between the stainless steel matrix and the hydrogen barrier layer, and between the stainless steel matrix and the first anti-corrosion layer, so that the hydrogen barrier layer and the first anti-corrosion layer are firmly bonded and not easy to fall off.

[0010] Optionally, the oxide powder includes α-Al2O3, SiO2, low-temperature glass powder and rare earth oxide; The mass ratio of α-Al2O3, SiO2, low-temperature glass powder and rare earth oxide is 1:(1.2-1.5):(1-1.5):(1-1.5); Specifically, the rare earth oxide includes La2O3 and / or CeO2.

[0011] Preferably, the mass ratio of La2O3 to CeO2 is (5~8):1.

[0012] Specifically, in the hydrogen barrier layer, the mass of the inorganic silicone adhesive is 7 to 9 times the total mass of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide.

[0013] Specifically, the inorganic silica adhesive includes sodium silicate, potassium silicate or calcium silicate.

[0014] Specifically, the present application defines the ratio of each component in the hydrogen barrier layer, and adds a specific ratio of modified graphene oxide and rare earth oxide to obtain a dense, stable, and highly hydrogen-barrier layer.

[0015] Specifically, both α-Al2O3 and SiO2 can effectively reduce the diffusion of hydrogen molecules. The addition of SiO2 can also promote the stability of the hydrogen barrier ceramic coating glaze. 3+ The formed aluminum oxide tetrahedrons and silicon oxide tetrahedrons work together to make the overall network structure tighter and further improve the hydrogen barrier performance; the addition of rare earth oxides can refine the grains, thereby improving the stability and hydrogen barrier performance. However, the dispersibility of rare earth oxides is poor, and the agglomeration of rare earth oxides has an adverse effect on the performance of the hydrogen barrier layer. The addition of modified graphene oxide with specific components can improve the dispersibility of rare earth oxides and obtain a hydrogen barrier layer with excellent hydrogen barrier performance.

[0016] Specifically, the mass of the inorganic silicone adhesive is 7 to 9 times the total mass of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxides; if there is too little inorganic silicone adhesive, interconnected pores are likely to exist in the coating, reducing the hydrogen permeation resistance of the coating, and may also cause the bonding strength with the transition layer to be too low, which may easily cause the coating to fall off; if there is too much inorganic silicone adhesive, the total mass of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxides is too small, the hydrogen permeation resistance is reduced, the brittleness of the coating is increased, and the mechanical properties are adversely affected.

[0017] The metal oxides include Cr2O3, Na2O, ZrO2, and Nb2O5; the mass ratio of Cr2O3, Na2O, ZrO2, and Nb2O5 is 1:(0.4~0.6):(0.3~0.5):(0.3~0.5).

[0018] Specifically, the enamel layer includes SiO2, metal oxides and borax, wherein the mass ratio of SiO2 to Cr2O3 is (1.5~2):1, and the mass ratio of borax to Cr2O3 is (0.4~0.5):1.

[0019] Optionally, the method for preparing the modified graphene oxide comprises the following steps: S1: dispersing graphene oxide in ethanol to obtain a graphene oxide dispersion; S2 adding a silane coupling agent to the graphene oxide dispersion obtained in step S1, heating and stirring; S3 is centrifuged and vacuum dried to obtain modified graphene oxide.

[0020] Optionally, the mass ratio of graphene oxide to ethanol is 1:(400-500); the volume fraction of the silane coupling agent is 1.1-2.1%.

[0021] Specifically, the dispersion time in step S1 is 20-30 minutes; the temperature in step S2 is 65-75° C., and the stirring time is 4-5 hours; the centrifugal speed in step S3 is 7500-8500 rpm, and the vacuum drying is 45-55° C. for 24-36 hours.

[0022] Specifically, graphene oxide modified with a silane coupling agent can improve the system dispersibility and interface bonding.

[0023] Specifically, the silane coupling agent is an aminosilane coupling agent.

[0024] Specifically, the aminosilane coupling agent is 3-aminopropyltriethoxysilane or N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.

[0025] Preferably, the aminosilane coupling agent is 3-aminopropyltriethoxysilane.

[0026] Specifically, the aminosilane coupling agent can introduce amine groups into graphene oxide, thereby improving and obtaining modified graphene oxide.

[0027] Specifically, the modified graphene oxide modified by a specific method can, on the one hand, serve as a hydrogen barrier structure and a hydrogen trap to play a role in hydrogen barrier; on the other hand, it helps to improve the dispersion of rare earth oxides and avoid their agglomeration, which is beneficial to improving the hydrogen barrier performance.

[0028] Optionally, in parts by weight, the first anti-corrosion coating includes 10-15 parts of inorganic silicone adhesive, 1.5-2 parts of α-Al2O3, 1-1.5 parts of SiO2, 0.5-1 parts of low-temperature glass powder and 1-3 parts of titanate coupling agent.

[0029] Specifically, the inorganic silica adhesive includes sodium silicate, potassium silicate or calcium silicate.

[0030] Specifically, the phthalate coupling agent includes isopropyl tri(dioctylpyrophosphate) titanate.

[0031] Specifically, by adding a specific proportion of titanate coupling agent, isopropyl tri(dioctyl pyrophosphate) titanate can undergo a hydrolysis reaction at high temperature to generate active hydroxyl groups, which, on the one hand, can produce a strong bonding force with the inorganic material in the first anti-corrosion coating; on the other hand, can react with the brominated epoxy resin in the second anti-corrosion coating to enhance the bonding force between the first anti-corrosion coating and the second anti-corrosion coating.

[0032] Optionally, the modified epoxy organic coating comprises, by weight, 25-35 parts of brominated epoxy resin, 0.05-0.15 parts of sulfonic acid group-modified graphene oxide, 0.25-0.5 parts of TiO2, 0.02-0.05 parts of polyethyleneimine and 20-30 parts of acetone.

[0033] Specifically, the modified epoxy coating uses brominated epoxy resin. The brominated epoxy resin has high bonding strength, tighter molecular folding, and steric hindrance when combined with methyl groups, which effectively blocks hydrogen penetration and diffusion. Graphene oxide and TiO2 are modified with sulfonic acid groups in a specific ratio. The synergistic effect of the two, on the one hand, makes the modified epoxy coating have higher hydrogen resistance; on the other hand, it can improve the corrosion resistance of the modified epoxy coating, so that it can adapt to long-term service in the submarine environment.

[0034] Specifically, the amino groups on polyethyleneimine react with the hydroxyl groups on the surface of TiO2, making the TiO2 surface positively charged, and the long-chain structure of polyethyleneimine helps to reduce the agglomeration of TiO2; on the other hand, polyethyleneimine interacts with brominated epoxy resin to further enhance the adhesion of the coating.

[0035] Optionally, the method for preparing the sulfonic acid group-modified graphene oxide comprises the following steps: S01: dissolve sodium lignin sulfonate in water, add graphene oxide, and perform ultrasonic treatment until it is completely dispersed; S02 was then condensed and refluxed in a water bath at 60-65°C, stirred for reaction for 3-5 hours, and then centrifuged and washed 3-5 times with anhydrous ethanol and deionized water respectively, and dried and stored to obtain sulfonic acid-modified graphene oxide.

[0036] Specifically, the mass ratio of sodium lignin sulfonate to graphene oxide in S01 is (1~2):1.

[0037] Specifically, during the modification process, sulfonic acid groups are introduced into the surface of graphene oxide, and the surface carries a negative charge, while the surface of TiO2 carries a positive charge. The difference in charge creates an electrostatic attraction between the two, which is beneficial for the formation of a stable composite structure between the two, reduces direct contact between TiO2, and prevents agglomeration. TiO2 and sulfonic acid-modified graphene oxide are stably dispersed; on the other hand, the interface compatibility between TiO2 and sulfonic acid-modified graphene oxide and brominated epoxy resin is also improved, thereby improving the overall performance of the coating.

[0038] According to another aspect of the present application, a method for preparing the above-mentioned corrosion-resistant hydrogen pipeline based on a stainless steel substrate is also provided, comprising the following steps: (1) Pretreatment of the stainless steel base tube: The surface of the stainless steel base tube is sandblasted, then ultrasonically cleaned in ethanol, and dried for later use; (2) Preparation of transition layer: The pretreated stainless steel substrate tube is used as a cathode and the nickel plate is used as an anode, and is placed in an electrolyte for electrodeposition to obtain a Ni-Ti-Ce layer; the electrolyte comprises micron titanium particles, nickel salt, cerium sulfate, a chelating agent, sodium chloride, a surfactant and a buffer; (3) Preparation of hydrogen barrier layer: coating a mixture of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide on the transition layer on the inner surface of the stainless steel substrate tube, and curing to obtain the hydrogen barrier layer; (4) Preparation of the enamel layer: coating an enamel glaze on the hydrogen barrier layer and sintering to obtain the enamel layer; the enamel glaze comprises SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax; (5) Preparation of the first anti-corrosion layer: coating a mixture of an inorganic silicone adhesive, α-Al2O3, SiO2, low-temperature glass powder and a titanate coupling agent on the transition layer on the outer surface of the stainless steel base tube, curing and sintering to obtain the first anti-corrosion layer; (6) Preparation of the second anti-corrosion layer: sulfonic acid modified graphene oxide and TiO2 are placed in acetone, polyethyleneimine is added, ultrasonic dispersion is performed, brominated epoxy resin is added, and the mixture is stirred evenly to obtain a modified epoxy organic coating. The modified epoxy organic coating is sprayed on the first anti-corrosion layer on the outer surface of the stainless steel substrate tube, and cured at room temperature to obtain a modified epoxy organic coating. Thus, an anti-corrosion hydrogen pipeline based on a stainless steel substrate is obtained.

[0039] Specifically, in step (1), the stainless steel substrate tube is first pretreated to remove surface oil and impurities to facilitate the subsequent bonding of the coating.

[0040] Specifically, in step (2), the preparation method of the electrolyte includes: dissolving nickel salt in pure water at room temperature, adding micron titanium particles, a complexing agent, a buffer, cerium sulfate, sodium chloride and a surfactant, and stirring evenly; The nickel salt includes nickel sulfate or nickel chloride; The complexing agent is one or more of citric acid, potassium pyrophosphate, and sodium pyrophosphate; The surfactant is one or more of 2-ethylhexyl sodium sulfate, sodium dodecyl sulfate, and alkylphenol polyoxyethylene ether sodium sulfate; The buffer is boric acid.

[0041] Specifically, cerium sulfate can further improve the corrosion resistance and oxidation resistance of the transition layer, and can also refine the grain structure, thereby improving the mechanical properties of the transition layer.

[0042] Specifically, boric acid as a buffer can adjust and stabilize the pH value of the electrolyte, preventing pH fluctuations from affecting the quality and process stability of the transition layer; boric acid can also inhibit hydrogen evolution and reduce pores and defects in the transition layer.

[0043] Specifically, the preparation method of the enamel glaze in step (4) comprises the following steps: adding SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax according to a proportion into a ball mill for mixing, placing the mixture into a heating furnace and heating it to 600-620°C, and keeping it warm for 15-20 minutes; then heating it to 1100-1200°C and keeping it warm for 30-40 minutes to obtain a molten enamel glaze; quenching the enamel glaze melt with water and drying it to obtain a frit; grinding the frit to obtain a powdered enamel glaze, and then adding ethanol to obtain the enamel glaze.

[0044] Specifically, in step (6), before spraying the modified epoxy organic coating, the step of filtering the modified epoxy organic coating is also included.

[0045] Optionally, the electrodeposition temperature in step (2) is 50-60°C and the current density is 10-50A / dm 2 , the deposition time is 10-20min; the electrolyte contains 70-80g / L of micron titanium particles, 0.5-0.9mol / L of nickel salt, 0.3-0.6g / L of cerium sulfate, 10-40g / L of complexing agent, 0.5-2mol / L of sodium chloride, 0.02-0.1g / L of surfactant and 0.2-0.6mol / L of buffer.

[0046] Optionally, in step (4), the sintering temperature is 750-850° C., and the sintering time is 5-10 min; in step (5), the sintering temperature is 650-700° C., and the sintering time is 15-20 min.

[0047] Specifically, after the hydrogen barrier layer is solidified, enamel glaze is applied and then sintered, which further enhances the bonding force between the hydrogen barrier layer and the enamel layer, forming the enamel layer and the glass-coated hydrogen barrier layer, which together achieve comprehensive hydrogen penetration resistance.

[0048] Specifically, the present application specifies the sintering temperature and sintering time to obtain a dense and smooth enamel layer, a glass-coated hydrogen barrier layer and a first anti-corrosion coating.

[0049] The beneficial effects of this application include but are not limited to: 1. According to the anti-corrosion hydrogen pipeline based on the stainless steel substrate of the present application, the technical effect of internal hydrogen resistance and external corrosion resistance is achieved by setting the inner surface coating and the outer surface coating; by setting the transition layer between the stainless steel substrate and the hydrogen resistance layer and between the stainless steel substrate and the first anti-corrosion layer, the transition layer and the stainless steel substrate, the hydrogen resistance layer, and the first anti-corrosion layer all have strong bonding force, so as to enhance the bonding force between the hydrogen resistance layer and the stainless steel, and the bonding force between the first anti-corrosion layer and the stainless steel substrate; the setting of the enamel layer achieves the first-step hydrogen resistance performance; the setting of the hydrogen resistance layer makes the stainless steel substrate submarine hydrogen pipeline have more excellent hydrogen resistance performance, improves the hydrogen resistance performance, and realizes comprehensive hydrogen penetration resistance together with the enamel layer; the first anti-corrosion layer and the second anti-corrosion layer work together, so that the stainless steel substrate submarine hydrogen pipeline can adapt to the working environment of the seabed and has strong corrosion resistance.

[0050] 2. According to the anti-corrosion hydrogen pipeline based on a stainless steel matrix of the present application, the ratio of the inorganic silicone adhesive, α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide is specifically defined, the hydrogen barrier layer formed has a high hydrogen barrier factor, and the preparation method of the modified graphene oxide is also defined. The addition of the modified graphene oxide, on the one hand, can serve as a hydrogen barrier structure and a hydrogen trap to play a hydrogen barrier role, and on the other hand, it helps to improve the dispersibility of the rare earth oxide, avoid its agglomeration, and is conducive to improving the hydrogen barrier performance.

[0051] 3. According to the anti-corrosion hydrogen pipeline based on stainless steel substrate of the present application, the modified epoxy organic coating adopts brominated epoxy resin, and the brominated epoxy resin has high bonding strength, tighter molecular folding, and stronger bonding force; a specific proportion of sulfonic acid group-modified graphene oxide and TiO2 are adopted, and the synergistic effect of the two can improve the corrosion resistance of the modified epoxy organic coating, so that it can adapt to long-term service in the submarine environment.

[0052] 4. According to the method for preparing a composite coating of a stainless steel substrate submarine hydrogen pipeline of the present application, the process steps are simple, the raw materials are easily available, and it is easy to promote and utilize. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 This is a schematic structural diagram of a corrosion-resistant hydrogen transmission pipeline based on a stainless steel substrate involved in an embodiment of the present application.

[0054] 1. Stainless steel base tube; 2. Transition layer; 3. Hydrogen barrier layer; 4. Enamel layer; 5. First anti-corrosion layer; 6. Second anti-corrosion layer. DETAILED DESCRIPTION

[0055] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0056] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.

[0057] Example 1 (1) Pretreatment of the stainless steel base tube: The surface of the stainless steel base tube is sandblasted, then ultrasonically cleaned in ethanol, and dried for later use; (2) Preparation of transition layer: The pretreated stainless steel substrate tube is used as the cathode and the nickel plate is used as the anode, and is placed in an electrolyte for electrodeposition to obtain a Ni-Ti-Ce layer; the electrolyte includes 70 g / L of micron titanium particles, 0.5 mol / L of nickel salt nickel sulfate, 0.3 g / L of cerium sulfate, 10 g / L of chelating agent citric acid, 0.5 mol / L of sodium chloride, 0.02 g / L of surfactant 2-ethylhexyl sodium sulfate, and 0.2 mol / L of buffer boric acid; The electrodeposition temperature was 50°C and the current density was 10A / dm 2 , the deposition time is 10 min; the thickness of the Ni-Ti-Ce layer is 10 μm; (3) Preparation of hydrogen barrier layer: a mixture of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide is coated on the surface of a stainless steel substrate tube, the mass ratio of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide La2O3 is 1:1.2:1:0.5:1, the mass of inorganic silica adhesive sodium silicate is 7 times the total mass of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide, sintering, the sintering temperature is 750°C, and the sintering time is 20 min; a hydrogen barrier layer is obtained; the thickness of the hydrogen barrier layer is 150 μm; (4) Preparation of enamel layer: coating enamel glaze on the hydrogen barrier layer and sintering to obtain an enamel layer with a thickness of 50 μm; the enamel glaze comprises SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax; wherein the mass ratio of SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax is 1.5:1:0.4:0.3:0.3:0.4; the sintering temperature is 750°C and the sintering time is 5 min; (5) Preparation of the first anti-corrosion layer: a mixture of 10 parts of inorganic silica adhesive sodium silicate, 1.5 parts of α-Al2O3, 1 part of SiO2, 0.5 parts of low-temperature glass powder and 1 part of titanate coupling agent isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is coated on the transition layer on the outer surface of the stainless steel substrate tube, cured at 60°C, and sintered to obtain a first anti-corrosion layer with a thickness of 50 μm. The sintering temperature is 650°C and the sintering time is 15 min. (6) Preparation of the second anti-corrosion layer: sulfonic acid modified graphene oxide and TiO2 are placed in acetone, polyethyleneimine is added, and ultrasonic dispersion is performed. Then, brominated epoxy resin is added, wherein, by weight, 25 parts of brominated epoxy resin, 0.05 parts of sulfonic acid modified graphene oxide, 0.25 parts of TiO2, 0.02 parts of polyethyleneimine and 20 parts of acetone are added. The mixture is stirred evenly to obtain a modified epoxy organic coating. The modified epoxy organic coating is sprayed on the first anti-corrosion layer on the outer surface of the stainless steel substrate pipe, and cured at room temperature to obtain a modified epoxy organic coating having a thickness of 300 μm. Thus, an anti-corrosion hydrogen transmission pipeline based on a stainless steel substrate is obtained.

[0058] The preparation method of modified graphene oxide is as follows: S1: dispersing graphene oxide in ethanol, wherein the mass ratio of graphene oxide to ethanol is 1:400, to obtain a graphene oxide dispersion, and the dispersion time is 20 min; S2: adding 3-aminopropyltriethoxysilane to the graphene oxide dispersion obtained in step S1, wherein the volume fraction of 3-aminopropyltriethoxysilane is 1.1%, heating and stirring, the temperature is 65° C., and the stirring time is 4 hours; S3 was centrifuged and vacuum dried to obtain modified graphene oxide. The centrifugal speed was 7500 rpm and the vacuum drying was performed at 45° C. for 24 h.

[0059] The preparation method of enamel glaze is as follows: SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax are added into a ball mill according to a proportion and mixed. The mixture is placed in a heating furnace and heated to 600°C and kept warm for 15 minutes; then heated to 1100°C and kept warm for 30 minutes to obtain molten enamel glaze; the enamel glaze melt is quenched with water and dried to obtain a frit; the frit is ground to obtain powdered enamel glaze, and then ethanol is added to obtain enamel glaze.

[0060] The preparation method of sulfonic acid group-modified graphene oxide is as follows: S01: dissolve sodium lignin sulfonate in water, add graphene oxide, and perform ultrasonic treatment until the dispersion is complete; the mass ratio of sodium lignin sulfonate to graphene oxide is 1:1; S02 was then condensed and refluxed in a water bath at 60°C, stirred and reacted for 3 hours, and then centrifuged and washed three times with anhydrous ethanol and deionized water respectively, and dried and stored to obtain sulfonic acid-modified graphene oxide.

[0061] Example 2 (1) Pretreatment of the stainless steel base tube: The surface of the stainless steel base tube is sandblasted, then ultrasonically cleaned in ethanol, and dried for later use; (2) Preparation of transition layer: The pretreated stainless steel substrate tube is used as the cathode and the nickel plate is used as the anode, and is placed in an electrolyte for electrodeposition to obtain a Ni-Ti-Ce layer; the electrolyte includes 80 g / L of micron titanium particles, 0.9 mol / L of nickel salt nickel sulfate, 0.6 g / L of cerium sulfate, 40 g / L of chelating agent citric acid, 2 mol / L of sodium chloride, 0.1 g / L of surfactant sodium dodecyl sulfate, and 0.6 mol / L of buffer boric acid; The electrodeposition temperature was 60°C and the current density was 50A / dm 2 , deposition time is 20min; Ni-Ti-Ce layer thickness is 15μm; (3) Preparation of hydrogen barrier layer: a mixture of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide is coated on the surface of a stainless steel substrate tube, the mass ratio of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide CeO2 is 1:1.5:1.5:0.8:1.5, the mass of inorganic silica adhesive calcium silicate is 9 times the sum of the mass of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide CeO2, sintering, the sintering temperature is 850°C, and the sintering time is 30 min; a hydrogen barrier layer is obtained; the thickness of the hydrogen barrier layer is 50 μm; (4) Preparation of enamel layer: coating enamel glaze on the hydrogen barrier layer and sintering to obtain an enamel layer with a thickness of 60 μm; the enamel glaze comprises SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax; wherein the mass ratio of SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax is 2:1:0.6:0.5:0.5:0.5; the sintering temperature is 850°C and the sintering time is 10 min; (5) Preparation of the first anti-corrosion layer: a mixture of 15 parts of inorganic silica adhesive calcium silicate, 2 parts of α-Al2O3, 1.5 parts of SiO2, 1 part of low-temperature glass powder and 3 parts of titanate coupling agent isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is coated on the transition layer on the outer surface of the stainless steel substrate tube, cured and sintered to obtain the first anti-corrosion layer with a thickness of 100 μm; the sintering temperature is 700°C and the sintering time is 20 min; (6) Preparation of the second anti-corrosion layer: sulfonic acid modified graphene oxide and TiO2 are placed in acetone, polyethyleneimine is added, and ultrasonic dispersion is performed. Then, brominated epoxy resin is added, which includes 35 parts of brominated epoxy resin, 0.15 parts of sulfonic acid modified graphene oxide, 0.5 parts of TiO2, 0.05 parts of polyethyleneimine and 30 parts of acetone in parts by weight. The mixture is stirred evenly to obtain a modified epoxy organic coating. The modified epoxy organic coating is sprayed on the first anti-corrosion layer on the outer surface of the stainless steel substrate pipe, and cured at room temperature to obtain a modified epoxy organic coating having a thickness of 200 μm. Thus, an anti-corrosion hydrogen transmission pipeline based on a stainless steel substrate is obtained.

[0062] The preparation method of modified graphene oxide is as follows: S1: dispersing graphene oxide in ethanol, wherein the mass ratio of graphene oxide to ethanol is 1:500, to obtain a graphene oxide dispersion, and the dispersion time is 30 min; S2: adding N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to the graphene oxide dispersion obtained in step S1, wherein the volume fraction of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 2.1%, heating and stirring, the temperature is 75° C., and the stirring time is 5 h; S3 was centrifuged and vacuum dried to obtain modified graphene oxide. The centrifugal speed was 8500 rpm and the vacuum drying was performed at 55° C. for 36 h.

[0063] The preparation method of enamel glaze is as follows: SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax are added into a ball mill according to a proportion and mixed. The mixture is placed in a heating furnace and heated to 620°C and kept warm for 20 minutes; then heated to 1200°C and kept warm for 40 minutes to obtain molten enamel glaze; the enamel glaze melt is quenched with water and dried to obtain a frit; the frit is ground to obtain powdered enamel glaze, and then ethanol is added to obtain enamel glaze.

[0064] The preparation method of sulfonic acid group-modified graphene oxide is as follows: S01: Sodium lignin sulfonate is dissolved in water, graphene oxide is added, and ultrasonication is performed until the dispersion is complete; the mass ratio of sodium lignin sulfonate to graphene oxide is 2:1; S02 was then condensed and refluxed in a 60°C water bath, stirred and reacted for 5 hours, and then centrifuged and washed 5 times with anhydrous ethanol and deionized water respectively, and dried and stored to obtain sulfonic acid-modified graphene oxide.

[0065] Example 3 (1) Pretreatment of the stainless steel base tube: The surface of the stainless steel base tube is sandblasted, then ultrasonically cleaned in ethanol, and dried for later use; (2) Preparation of transition layer: The pretreated stainless steel substrate tube is used as the cathode and the nickel plate is used as the anode, and is placed in an electrolyte for electrodeposition to obtain a Ni-Ti-Ce layer; the electrolyte includes 80 g / L of micron titanium particles, 0.7 mol / L of nickel salt nickel chloride, 0.5 g / L of cerium sulfate, 20 g / L of chelating agent citric acid, 1 mol / L of sodium chloride, 0.05 g / L of surfactant sodium dodecyl sulfate, and 0.4 mol / L of buffer boric acid; The electrodeposition temperature was 50°C and the current density was 10A / dm 2 , the deposition time is 20min; the thickness of the Ni-Ti-Ce layer is 15μm; (3) Preparation of hydrogen barrier layer: a mixture of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide is coated on the surface of a stainless steel substrate tube, the mass ratio of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide is 1:1.2:1.5:0.8:1, the rare earth oxide includes La2O3 and CeO2, the mass ratio of La2O3 and CeO2 is 5:1, the mass of inorganic silica adhesive sodium silicate is 8 times the mass of α-Al2O3, SiO2, low-temperature glass powder, modified graphene oxide and rare earth oxide, sintering, the sintering temperature is 800°C, and the sintering time is 25 min; a hydrogen barrier layer is obtained; the thickness of the hydrogen barrier layer is 100 μm; (4) Preparation of enamel layer: coating enamel glaze on the hydrogen barrier layer and sintering to obtain an enamel layer with a thickness of 50 μm; the enamel glaze comprises SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax; wherein the mass ratio of SiO2, Cr2O3, Na2O, ZrO2, Nb2O5 and borax is 1.5:1:0.5:0.4:0.5:0.4; the sintering temperature is 800°C and the sintering time is 5 min; (5) Preparation of the first anti-corrosion layer: a mixture of 10 parts of inorganic silica adhesive sodium silicate, 1.5 parts of α-Al2O3, 1.5 parts of SiO2, 1 part of low-temperature glass powder and 2 parts of titanate coupling agent isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is coated on the transition layer on the outer surface of the stainless steel substrate tube, cured and sintered to obtain the first anti-corrosion layer with a thickness of 80 μm. The sintering temperature is 650°C and the sintering time is 15 min. (4) Preparation of the second anti-corrosion layer: sulfonic acid modified graphene oxide and TiO2 are placed in acetone, polyethyleneimine is added, and ultrasonic dispersion is performed. Then, brominated epoxy resin is added, which includes 30 parts of brominated epoxy resin, 0.1 parts of sulfonic acid modified graphene oxide, 0.3 parts of TiO2, 0.03 parts of polyethyleneimine and 30 parts of acetone in parts by weight. The mixture is stirred evenly to obtain a modified epoxy organic coating. The modified epoxy organic coating is sprayed on the first anti-corrosion coating on the outer surface of the stainless steel substrate pipe, and cured at room temperature to obtain a modified epoxy organic coating having a thickness of 200 μm. Thus, an anti-corrosion hydrogen transmission pipeline based on a stainless steel substrate is obtained.

[0066] The preparation method of modified graphene oxide is as follows: S1: dispersing graphene oxide in ethanol, wherein the mass ratio of graphene oxide to ethanol is 1:450, to obtain a graphene oxide dispersion, and the dispersion time is 30 min; S2: adding 3-aminopropyltriethoxysilane to the graphene oxide dispersion obtained in step S1, wherein the volume fraction of 3-aminopropyltriethoxysilane is 1.5%, heating and stirring, the temperature is 75° C., and the stirring time is 5 h; S3 was centrifuged and vacuum dried to obtain modified graphene oxide. The centrifugal speed was 8500 rpm and the vacuum drying was performed at 55° C. for 36 h.

[0067] The preparation method of sulfonic acid group-modified graphene oxide is as follows: S01: Sodium lignin sulfonate is dissolved in water, graphene oxide is added, and ultrasonication is performed until the dispersion is complete; the mass ratio of sodium lignin sulfonate to graphene oxide is 1.5:1; S02 was then condensed and refluxed in a 60°C water bath, stirred and reacted for 3 hours, and then centrifuged and washed 5 times with anhydrous ethanol and deionized water respectively, and dried and stored to obtain sulfonic acid-modified graphene oxide.

[0068] Example 4 The difference between Example 4 and Example 3 is that the oxide powder does not include rare earth oxides, and the rest are the same.

[0069] Example 5 The difference between Example 5 and Example 3 is that the rare earth oxide is Er2O3, and the rest are the same.

[0070] Example 6 The difference between Example 6 and Example 3 is that the mass ratio of La2O3 to CeO2 is 1:1, and the rest are the same.

[0071] Example 7 The difference between Example 7 and Example 3 is that in the preparation of modified graphene oxide, the silane coupling agent is KH560, and the rest are the same.

[0072] Example 8 The difference between Example 8 and Example 3 is that step (5) does not include a titanate coupling agent, and the rest are the same.

[0073] Example 9 The difference between Example 9 and Example 3 is that ordinary epoxy resin is used instead of non-brominated epoxy resin, and the rest are the same.

[0074] Example 10 The difference between Example 10 and Example 3 is that the sulfonic acid group-modified graphene oxide is 0.4 parts, TiO2 is not included, and the rest are the same.

[0075] Embodiment 11 The difference between Example 11 and Example 3 is that 0.4 parts of TiO2 are used, sulfonic acid group-modified graphene oxide is not included, and the rest are the same.

[0076] Example 12 The difference between Example 12 and Example 3 is that graphene oxide is used instead of sulfonic acid group-modified graphene oxide, and the rest are the same.

[0077] Embodiment 13 The difference between Example 13 and Example 3 is that cerium sulfate is not included in the electrolyte, and the rest is the same.

[0078] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that step (2) is not included, that is, the inner surface coating and the outer surface coating do not include a transition layer, and the rest are the same.

[0079] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that step (4) is not included, that is, the enamel layer is not included, and the rest is the same.

[0080] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that step (5) is not included, that is, the first anti-corrosion layer is not included, and the rest is the same.

[0081] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that step (3) does not include modified graphene oxide, and the rest are the same.

[0082] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that the modified graphene oxide in step (3) is not modified and is graphene oxide, and the rest is the same.

[0083] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that the second anti-corrosion layer is not included, and the rest is the same.

[0084] Experimental example 1. Hydrogen barrier performance test A hydrogen permeation container experimental device was used to carry out a hydrogen permeation resistance test and calculate the hydrogen permeability reduction factor (PRF). A coating density tester was used to carry out a density test. The test results are shown in Table 1.

[0085] Table 1 Hydrogen barrier and density test results

[0086] 2. Bonding strength test The tensile strength of the coating was determined by using a universal testing machine using the adhesion tensile method. The test results are shown in Table 2.

[0087] Table 2 Bonding strength test

[0088] 3. Salt spray resistance test A 3.5wt% NaCl solution was used to simulate the seawater environment, and a spray test was performed according to the ASTM B117 standard to evaluate the corrosion resistance of the coating in a simulated marine atmospheric environment. In the experimental setting, the coating sample was placed in a dedicated salt spray test chamber and continuously exposed to high salinity conditions. The test temperature was 30-40°C. The concentration of the 3.5wt% NaCl solution was kept constant during the test, and the test time reached 1000h to simulate the impact of long-term marine climate. The coating samples included surface scratches and no scratches. The test results are shown in Table 3.

[0089] Table 3 Salt spray resistance test

[0090] According to Tables 1 to 3, the composite coatings obtained in Examples 1 to 3 have a high hydrogen permeability reduction factor and density, wherein the highest hydrogen permeability reduction factor is 1025, and the highest density is 99.5%; and have good salt spray resistance, and can meet the requirements of long-term service in the submarine environment. Compared with Example 3, Comparative Example 1 does not include a transition layer, which seriously affects the hydrogen barrier performance and bonding strength of the composite coating; Compared with Example 3, the hydrogen barrier performance, bonding strength and salt spray resistance of Comparative Example 6 have decreased to varying degrees, among which the impact on salt spray resistance is the greatest, indicating that it is difficult to adapt to the submarine service environment; Examples 4 to 7, Comparative Examples 1 to Comparative Example 2, Comparative Example 4 to Comparative Example 5 have significantly decreased hydrogen barrier performance; Examples 8, Example 13, Comparative Example 1, and Comparative Example 3 have significantly decreased bonding performance; Examples 10 to 12, Comparative Example 3 and Comparative Example 6 have decreased corrosion resistance.

[0091] like Figure 1As shown, by arranging the transition layer 2 between the stainless steel substrate 1 and the hydrogen barrier layer 3 and between the stainless steel substrate 1 and the first anti-corrosion layer 5, the transition layer 2 and the stainless steel substrate 1, the hydrogen barrier layer 3, and the first anti-corrosion layer 5 all have a strong bonding force, so as to enhance the bonding force between the hydrogen barrier layer 3 and the stainless steel substrate 1, and the bonding force between the first anti-corrosion layer 5 and the stainless steel substrate 1; the enamel layer 4 is arranged to achieve the first step of hydrogen barrier performance; the hydrogen barrier layer 3 is arranged to make the stainless steel substrate submarine hydrogen pipeline have more excellent hydrogen barrier performance, improve the hydrogen barrier performance, and achieve comprehensive hydrogen penetration resistance together with the enamel layer 4; the first anti-corrosion layer 5 and the second anti-corrosion layer 6 work together to enable the stainless steel substrate submarine hydrogen pipeline to adapt to the working environment of the seabed and have strong corrosion resistance.

[0092] The above is only an embodiment of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A corrosion-resistant hydrogen pipeline based on a stainless steel substrate. It is characterized in that It comprises a stainless steel base tube and an inner surface coating and an outer surface coating arranged on the stainless steel base tube; The inner surface coating includes, from the inside to the outside, an enamel layer, a hydrogen barrier layer and a transition layer in sequence; the outer surface coating includes, from the inside to the outside, a transition layer, a first anti-corrosion layer and a second anti-corrosion layer in sequence; The transition layer is a Ni-Ti-Ce layer; The hydrogen barrier layer is prepared from inorganic silica adhesive, modified graphene oxide and oxide powder; The enamel layer is made of SiO 2 , metal oxides and borax; The first anti-corrosion layer is composed of inorganic silicone adhesive, α-Al 2 O 3 、SiO 2 , low-temperature glass powder and titanate coupling agent; The second anti-corrosion layer is a modified epoxy organic coating.

2. The anti-corrosion hydrogen pipeline based on a stainless steel substrate according to claim 1, It is characterized in that The oxide powder includes α-Al 2 O 3 、SiO 2 , low temperature glass powder and rare earth oxides; The α-Al 2 O 3 、SiO 2 , the mass ratio of low temperature glass powder and rare earth oxide is 1:(1.2~1.5):(1~1.5):(1~1.5); The metal oxide includes Cr 2 O 3 、Na 2 O, ZrO 2 , Nb 2 O 5 ; The Cr 2 O 3 、Na 2 O, ZrO 2 , Nb 2 O 5 The mass ratio is 1:(0.4~0.6):(0.3~0.5):(0.3~0.5).

3. The anti-corrosion hydrogen pipeline based on a stainless steel substrate according to claim 1, It is characterized in that The preparation method of the modified graphene oxide comprises the following steps: S1: dispersing graphene oxide in ethanol to obtain a graphene oxide dispersion; S2: adding a silane coupling agent to the graphene oxide dispersion obtained in step S1, heating and stirring; S3 is centrifuged and vacuum dried to obtain modified graphene oxide.

4. The anti-corrosion hydrogen pipeline based on a stainless steel substrate according to claim 3, It is characterized in that The mass ratio of graphene oxide to ethanol is 1:(400-500); the volume fraction of the silane coupling agent is 1.1-2.1%.

5. The anti-corrosion hydrogen pipeline based on a stainless steel substrate according to claim 1, It is characterized in that According to the weight percentage, the first anti-corrosion coating includes 10-15 parts of inorganic silicone adhesive, α-Al 2 O 3 1.5~2 parts, SiO 2 1~1.5 parts, low-temperature glass powder 0.5~1 parts and titanate coupling agent 1~3 parts.

6. The anti-corrosion hydrogen pipeline based on a stainless steel substrate according to claim 1, It is characterized in that According to the weight percentage, the modified epoxy organic coating includes 25-35 parts of brominated epoxy resin, 0.05-0.15 parts of sulfonic acid group-modified graphene oxide, and TiO 2 0.25-0.5 parts, polyethyleneimine 0.02-0.05 parts and acetone 20-30 parts.

7. The anti-corrosion hydrogen pipeline based on a stainless steel substrate according to claim 6, It is characterized in that The preparation method of the sulfonic acid group-modified graphene oxide comprises the following steps: S01: dissolve sodium lignin sulfonate in water, add graphene oxide, and perform ultrasonic treatment until it is completely dispersed; S02 was then condensed and refluxed in a water bath at 60-65°C, stirred for reaction for 3-5 hours, and then centrifuged and washed 3-5 times with anhydrous ethanol and deionized water respectively, and dried and stored to obtain sulfonic acid-modified graphene oxide.

8. A method for preparing a corrosion-resistant hydrogen pipeline based on a stainless steel substrate according to any one of claims 1 to 7, It is characterized in that The following steps are involved: (1) Pretreatment of the stainless steel base tube: The surface of the stainless steel base tube is sandblasted, then ultrasonically cleaned in ethanol, and dried for later use; (2) Preparation of transition layer: The pretreated stainless steel substrate tube is used as a cathode and the nickel plate is used as an anode, and is placed in an electrolyte for electrodeposition to obtain a Ni-Ti-Ce layer; the electrolyte comprises micron titanium particles, nickel salt, cerium sulfate, a chelating agent, sodium chloride, a surfactant and a buffer; (3) Preparation of hydrogen barrier layer: α-Al 2 O 3 、SiO 2 , a mixture of low-temperature glass powder, modified graphene oxide and rare earth oxide is coated on the transition layer on the inner surface of the stainless steel substrate tube, and solidified to obtain a hydrogen barrier layer; (4) Preparation of enamel layer: coating enamel glaze on the hydrogen barrier layer and sintering to obtain enamel layer; the enamel glaze includes SiO 2 Cr 2 O 3 、Na 2 O, ZrO 2 , Nb 2 O 5 and borax; (5) Preparation of the first anti-corrosion layer: Inorganic silicone adhesive, α-Al 2 O 3 、SiO 2 , coating a mixture of low-temperature glass powder and titanate coupling agent on the transition layer on the outer surface of the stainless steel base tube, curing, and sintering to obtain a first anti-corrosion layer; (6) Preparation of the second anti-corrosion layer: Sulfonic acid-modified graphene oxide and TiO 2 Place it in acetone, add polyethyleneimine, ultrasonically disperse it, add brominated epoxy resin, stir it evenly to obtain a modified epoxy organic coating, spray the modified epoxy organic coating on the first anti-corrosion layer on the outer surface of the stainless steel substrate pipe, and cure it at room temperature to obtain a modified epoxy organic coating; thus, an anti-corrosion hydrogen pipeline based on a stainless steel substrate is obtained.

9. A method for preparing a corrosion-resistant hydrogen pipeline based on a stainless steel substrate according to claim 8, It is characterized in that Step (2) The electrodeposition temperature is 50-60°C and the current density is 10-50A / dm 2 , the deposition time is 10-20min; the electrolyte contains 70-80g / L of micron titanium particles, 0.5-0.9mol / L of nickel salt, 0.3-0.6g / L of cerium sulfate, 10-40g / L of complexing agent, 0.5-2mol / L of sodium chloride, 0.02-0.1g / L of surfactant and 0.2-0.6mol / L of buffer.

10. The method for preparing a corrosion-resistant hydrogen pipeline based on a stainless steel substrate according to claim 8, It is characterized in that In step (4), the sintering temperature is 750-850°C, and the sintering time is 5-10 min; in step (5), the sintering temperature is 650-700°C, and the sintering time is 15-20 min.

Citation Information

Patent Citations

  • Silicon carbide hydrogen permeation barrier coating for stainless steel and preparation method for silicon carbide hydrogen permeation barrier coating

    CN105525273A

  • Method for preparing silicon dioxide hydrogen-resistant coatings on inner walls of 316L stainless steel pipelines

    CN112756238A

  • Hydrogen permeation-resistant composite vitreous barrier layer for stainless steel substrate and preparation method and application of hydrogen permeation-resistant composite vitreous barrier layer

    CN116200743A

  • Processing method of gas cylinder enamel label

    CN117265535A

  • A method for coating enamel layer on the surface of cold-rolled steel sheet

    KR1019990071044A

Cited By

  • Hydrogen-resistant coating as well as preparation method and application thereof

    CN120830104A